Model predictive control of bidirectional isolated DC-DC converter for energy conversion system - Akter P.; Uddin M.; Mekhilef S.; Tan N.M.L.; Akagi H. (Taylor and Francis Ltd., 2023)
Cost functions; DC transformers; Electric load flow; Electric power factor; Energy conversion; Energy transfer; High frequency transformers; HVDC power transmission; MATLAB; Model predictive control; Power control; Predictive control systems; Reactive power; Voltage control; Bidirectional DC-DC converters; Bidirectional isolated dc-dc converter; Energy conversion systems; Full-bridge dc-dc converters; Power conversion systems; Predictive control; Predictive control algorithm; Unity power factor; DC-DC converters